Relaciones interpersonales y el consumo de alcohol en adolescentes - Macas Zhicay, Adriana Nicole (2024)
During the stage of adolescence, physical and emotional changes can be experienced, which can affect interpersonal relationships for prone alcohol consumption, social bonds determine a predisposing factor for light or serious consumption, and family relationships, in the same way, is a factor that affects alcohol intake during adolescence. The current work had a quantitative approach, with a non-experimental cross-sectional design that included a total of 44 articles between 2013 and 2023 at the beginning of the research. In order to determine a sample, non-probabilistic sampling was followed, the selection depended on exclusion and inclusion criteria, through which 15 documents were selected, relationships with the topic under investigation, and the prism instrument was used. Various sources of information were analyzed in English and Spanish languages with a longevity of 10 years. Based on the general objective of describing the scientific evidence of interpersonal relationships and alcohol consumption in adolescents, it was concluded that more than half of the population has had excessive alcohol consumption, with a greater frequency of interpersonal relationships such as intimate relationships, superficial, family relationships and need for inclusion, with the highest prevalence found in the countries Mexico, Spain and Ecuador. Regarding the consequences, interpersonal relationships and excessive alcohol consumption are what were most prevalent in all studies. An informative guide is designed, which aims to understand the advantages and risks of interpersonal relationships and their impact on alcohol consumption in adolescents, to make informed and responsible decisions, and present intervention strategies at a preventive level